2015
DOI: 10.3389/fped.2015.00034
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Gestational Diabetes Mellitus Risk in South Indian Women Based on MTHFR (C677T) and FVL (G1691A) Mutations

Abstract: We aimed to scrutinize the extent to which single amino acid substitutions in the MTHFR and factor V Leiden (FVL) genes affect the risk of gestational diabetes mellitus (GDM) in pregnant women of South Indian descendant. This case–control study was implemented once the ethical approval has been obtained. Overall, 237 women were recruited in this study: 137 had been diagnosed with GDM and the remaining 100 women were used as normal controls or non-GDM. The diagnosis of GDM was confirmed with biochemical analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
15
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 38 publications
2
15
0
Order By: Relevance
“…DNA was routinely purified at Kamineni Hospitals using a salting out procedure (12,13). The region 173 bp upstream of the GCK coding region was genotyped with polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) analysis.…”
Section: Mutational Analysismentioning
confidence: 99%
“…DNA was routinely purified at Kamineni Hospitals using a salting out procedure (12,13). The region 173 bp upstream of the GCK coding region was genotyped with polymerase chain reaction (PCR) and restriction fragment length polymorphism (RFLP) analysis.…”
Section: Mutational Analysismentioning
confidence: 99%
“…A combination of human genome sequencing and single nucleotide polymorphism (SNP) has provided the required amount of genetic data for human diseases (Romero-Sánchez et al, 2015). Numerous studies have verified homocysteine as an important biomarker in human diseases, along with the biological function in the folate metabolism pathway (Wang et al, 2016), and it plays a pivotal role in the irreversible conversion of 5, 10methylenetetrahydrofolate to 5methylenetetrahydrofolate, which converts the remethylation of homocysteine to methionine (Khan et al, 2015). Primarily, there are C677T and A1298C SNPs, which are commonly studied in global populations along with meta-analysis studies of human diseases.…”
Section: Introductionmentioning
confidence: 99%
“…However, not all pregnant women developed GDM even although they exposed to the same risks of GDM, which indicated that the genetic influences might contribute to the development of GDM . Cumulative evidence suggested that the genetic mutations contributed to the development of GDM, including KCNQ1, MTHFR, FVL, and CDKN2A …”
Section: Introductionmentioning
confidence: 99%
“…2 Cumulative evidence suggested that the genetic mutations contributed to the development of GDM, including KCNQ1, MTHFR, FVL, and CDKN2A. [3][4][5][6] The cyclin-dependent Kinase Inhibitor 2A (CDKN2A), one member in cyclin-dependent kinase family, is at chromosome 9, band p21.3 in human. It is reported that several variations of CDKN2A have associated with diabetes.…”
mentioning
confidence: 99%